2020
DOI: 10.1093/bib/bbaa285
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of SMN1–ACE/ACE2 interactions hinted at a potential protective effect of spinal muscular atrophy against COVID-19-induced lung injury

Abstract: Patients with spinal muscular atrophy (SMA) are susceptible to the respiratory infections and might be at a heightened risk of poor clinical outcomes upon contracting coronavirus disease 2019 (COVID-19). In the face of the COVID-19 pandemic, the potential associations of SMA with the susceptibility to and prognostication of COVID-19 need to be clarified. We documented an SMA case who contracted COVID-19 but only developed mild-to-moderate clinical and radiological manifestations of pneumonia, which were reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This study, our clinical experience, and the limited available body of evidence suggest that COVID-19, particularly with severe outcomes, was uncommon in patients with NMD during and after the first pandemic wave: in a Spanish paediatric NMD registry, 29 individuals tested positive for SARS-CoV-2 to November 2020: 10% were hospitalised and 3% were admitted to ICU. 13 In addition, in a cohort of 56 patients with spinal muscular atrophy in Hubei province, only one developed COVID-19, 21 and in a small study of 7 patients with Duchenne muscular dystrophy and COVID-19 infection confirmed on PCR testing, no patients developed moderate–severe disease despite complications including cardiomyopathy and respiratory failure. 12 …”
Section: Discussionmentioning
confidence: 99%
“…This study, our clinical experience, and the limited available body of evidence suggest that COVID-19, particularly with severe outcomes, was uncommon in patients with NMD during and after the first pandemic wave: in a Spanish paediatric NMD registry, 29 individuals tested positive for SARS-CoV-2 to November 2020: 10% were hospitalised and 3% were admitted to ICU. 13 In addition, in a cohort of 56 patients with spinal muscular atrophy in Hubei province, only one developed COVID-19, 21 and in a small study of 7 patients with Duchenne muscular dystrophy and COVID-19 infection confirmed on PCR testing, no patients developed moderate–severe disease despite complications including cardiomyopathy and respiratory failure. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated an interaction between the survival motor neuron 1 (SMN1) gene and the loss of function of the SMN protein, which is involved in ribonucleoprotein synthesis, intra- and intercellular trafficking of vesicles and organelles, and ACE/ACE2 expression [ 182 , 183 ].…”
Section: Renin-angiotensin-aldosterone System and Motor Neuron Diseasementioning
confidence: 99%
“…The authors of the study concluded that the protective role of young age seemed to outweigh the risk factors associated with having a neuromuscular condition [39]. Interestingly, a bioinformatics analysis investigating the possible interaction between the SMN gene and ACE2, a receptor involved in SARS-CoV-2 entry into the cell, suggests that SMN1 deficiency may modulate ACE2 levels and therefore have a direct impact on the pathogenesis of COVID-19 [69].…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%